2017
DOI: 10.3892/etm.2017.5435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium dobesilate on Nrf2, Keap1 and HO-1 in the lenses of D-galactose-induced cataracts in rats

Abstract: Abstract. This study investigated the effects of calcium dobesilate on Nrf2, Keap1 and HO-1 in the lenses of D-galactose-induced cataracts in rats. Thirty Sprague-Dawley rats were randomly divided into three groups: a blank control group, a model control group and a model administration group. A normal diet was given to the rats in the blank control group and the rats with D-galactose-induced cataracts of the model control group. Calcium dobesilate was also given to the rats with D-galactose-induced cataracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Decreased Keap1 would be predicted to increase Nrf2. However, the Nrf2 regulatory network is complex 5 , and these data suggest that other factors including reduced IQGAP predominate to lower Nrf2 levels in TRPM2 depletion 35,42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Decreased Keap1 would be predicted to increase Nrf2. However, the Nrf2 regulatory network is complex 5 , and these data suggest that other factors including reduced IQGAP predominate to lower Nrf2 levels in TRPM2 depletion 35,42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, CaD inhibits gentamicin-induced nephrotoxicity by increasing the reducing/antioxidant tissue ferric potency [ 29 ]. Finally, a recent study established that CaD has beneficial effects against D-gal-induced cataracts in rats by stabilizing the oxidant/antioxidant balance of the lens and improving the signaling of Nrf2-Keap1, a key regulator of oxidative status in vivo [ 38 ]. The present results demonstrated that CaD reduced cerebral oxidative stress, as revealed from its effects on MDA levels, as well as SOD, GPx, and CAT activity, suggesting the potential therapeutic use of CaD as an antioxidant/protective drug in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, Nrf2 plays a protective role by enabling the expression of downstream antioxidant genes and the antioxidant enzyme HO-1 ( 28 ). Oxidative stress in the skin not only changes the structure and function of proteins, lipids, and DNA at the molecular level, but also activates the mitogen-activated protein kinase pathway, nuclear transcription factor pathway, signal transduction, and activating transcription factor pathways at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%